A Study on Gen Z’s Attitude Towards Village/Rural Lifestyle in Ahmedabad City - Harshil Prajapati; Priyanshu Jani; Jignesh Vidani (International Journal of Global Sustainable Research, 2024)
This study explores the attitudes of Generation Z towards rural lifestyles in Ahmedabad, focusing on the perceptions, familiarity, and significance of rural life among urban youth. Given the rapid urbanization and the increasing digital connectivity of younger generations, it is crucial to understand how urban youth perceive rural areas, especially in terms of their cultural, economic, and social values. Through a series of hypotheses tested using statistical methods, the study examines associations between age, familiarity with rural life, and the belief in the cultural significance of rural areas. The findings reveal that while Generation Z acknowledges rural areas as an important part of India’s culture and heritage, their direct engagement with rural life remains minimal. The study highlights that urban upbringing, media influence, and digital connectivity are the primary factors shaping their perceptions. A lack of significant correlations between age and rural perceptions suggests that Generation Z's attitudes are not strongly influenced by age-related differences, but rather by external factors like media representations and limited firsthand experiences. The study also underscores the need for targeted programs and educational initiatives to bridge the urban-rural divide by promoting rural engagement and digital infrastructure in rural areas. The findings have practical implications for policymakers, educators, and rural development organizations aiming to foster a more balanced understanding of rural life among urban youth